HIV Stigma and Unprotected Sex among PLWH in KwaZulu-Natal, South Africa: A Longitudinal Exploration of Mediating Mechanisms - Earnshaw, Valerie A. (2014)
Social and structural factors including HIV stigma are theorized to drive global disparities in HIV prevalence. This study tests whether HIV self-stigma, or experiences of stigma at the individual level, is associated with engagement in unprotected sex among PLWH in KwaZulu-Natal, South Africa, where 37.4% of adults are living with HIV compared with 0.8% worldwide. It further explores whether depressive symptoms, HIV status disclosure to sex partners, and/or condom use attitudes mediate potential associations between HIV self-stigma and unprotected sex. Participants, including 924 PLWH, were recruited from primary care clinics and completed baseline, 6-, 12-, and 18- month survey assessments between 2008 and 2011. Hierarchical linear modeling analyses were used to examine longitudinal within-subjects associations between HIV self-stigma, mediators, and unprotected sex with both HIV-negative/unknown and HIV-positive partners. Results demonstrate that HIV self-stigma was prospectively associated with greater likelihood of unprotected sex with HIV-negative/unknown partners. None of the variables explored significantly mediated this association. HIV self-stigma was also prospectively associated with greater likelihood of unprotected sex with HIV-positive partners via the mediators of greater depressive symptoms and more negative condom use attitudes. The current study suggests that HIV self-stigma undermines HIV secondary prevention and care efforts among PLWH in KwaZulu-Natal. It is therefore critical to address HIV stigma at the social/structural level to reduce HIV self-stigma at the individual level and ultimately curb global disparities in HIV prevalence. In the absence of widespread social/structural change, interventions that treat depressive symptoms and encourage more positive condom use attitudes despite the existence of HIV stigma may buffer associations between HIV self-stigma and unprotected sex with HIV-positive partners among PLWH in KwaZulu-Natal.